Problematic Internet Usage self-control dilemmas: The opposite effects of commitment and progress framing cues on perceived value of internet, academic and social behaviors. (May 2018) - Dunbar, David; Proeve, Michael; Roberts, Rachel
Abstract: Problem Internet Usage (PIU) is a growing public health concern and despite an upsurge in research, there is limited information regarding effective psychological interventions. A model of the dynamics of self-regulation may provide a useful framework for psychological intervention with PIU. The model describes two patterns that individuals may follow when choosing goal directed behaviors, according to whether they hold commitment or progress frameworks. The model explains and predicts how opposite behavior outcomes can be achieved by holding commitment or progress frameworks. Three online studies tested the model in the context of PIU using a student population. Incongruent goal behavior was operationalised as internet activity and congruent goal behaviors as academic and social activities. Study 1 (N = 173) tested priming of commitment or progress frameworks and examined what effects positive and negative feedback had on subsequent behavior intentions. Study 2 (N = 167) examined high versus uncertain goal engagement priming effects and whether focusing on accomplished or unaccomplished actions produced the opposite behavior intentions. Study 3 (N = 172) tested if focusing on an abstract goal versus concrete steps would prime commitment or progress frameworks. Results supported the model's predictions for the framing cues and subsequent opposite behaviors for internet and academic activities with moderate and large effects. No support was found for predictions of social activities. Results of the study provide support for the self-regulation model in a clinical domain. Results may inform clinical interventions for PIU, demonstrating how opposite behavior outcomes may be achieved for the same scenarios given different underlying mental frameworks, and indicating how those frameworks may be cued in the first place. Highlights: Goals can be represented as commitment to, or progress towards, a desired end state. Commitment and progress representations cause different behavior evaluations. Certain cues can prime these representation frameworks. Positive and negative goal attainment cause opposite behavior outcomes for progress and commitment frames.